The zero curvature equation for rigid CR-manifolds. Issue 4 (2nd April 2016) - Ezhov, V.; Schmalz, G.
Abstract : In this paper, we present the general analytic solution to the zero curvature equation for rigid three-dimensional CR-manifolds. The solutions are uniquely determined by one function and four real parameters.